Organic Chemistry with a Biological Emphasis Volume II - Soderberg, Tim; Open Textbook Library (Open Textbook Library, 2016)
The traditional approach to teaching Organic Chemistry, taken by most of the textbooks that are currently available, is to focus primarily on the reactions of laboratory synthesis, with much less discussion - in the central chapters, at least - of biological molecules and reactions. This is despite the fact that, in many classrooms, a majority of students are majoring in Biology or Health Sciences rather than in Chemistry, and are presumably taking the course in order to learn about the chemistry that takes place in living things. In an effort to address this disconnect, I have developed a textbook for a two-semester, sophomore-level course in Organic Chemistry in which biological chemistry takes center stage. For the most part, the text covers the core concepts of organic structure, structure determination, and reactivity in the standard order. What is different is the context: biological chemistry is fully integrated into the explanation of central principles, and as much as possible the in-chapter and end-of-chapter problems are taken from the biochemical literature. Many laboratory synthesis reactions are also covered, generally in parallel with their biochemical counterparts - but it is intentionally the biological chemistry that comes first.
Chapter 9: Phosphate transfer reactions -- Section 1: Overview of phosphate groups -- Section 2: Phosphate transfer reactions - an overview -- Section 3: ATP, the principal phosphate group donor -- Section 4: Phosphorylation of alcohols -- Section 5: Phosphorylation of carboxylates -- Section 6: Hydrolysis of organic phosphates -- Section 7: Phosphate diesters in DNA and RNA -- Section 8: The organic chemistry of genetic engineering -- Chapter 10: Nucleophilic carbonyl addition reactions -- Section 1: Nucleophilic additions to aldehydes and ketones: an overview -- Section 2: Hemiacetals, hemiketals, and hydrates -- Section 3: Acetals and ketals -- Section 4: N-glycosidic bonds -- Section 5: Imines -- Section 5: A look ahead: addition of carbon and hydride nucleophiles to carbonyls -- Chapter 11: Nucleophilic acyl substitution reactions -- Section 1: Carboxylic acid derivatives -- Section 2: The nucleophilic acyl substitution mechanism -- Section 3: The relative reactivity of carboxylic acid derivatives -- Section 4: Acyl phosphates -- Section 5: Formation of thioesters, esters, and amides -- Section 6: Hydrolysis of thioesters, esters, and amides -- Section 7: Protein synthesis on the ribosome -- Section 8: Nucleophilic substitution at activated amides and carbamides -- Section 9: Nucleophilic acyl substitution reactions in the laboratory -- Section 10: A look ahead: acyl substitution reactions with a carbanion or hydride ion nucleophile -- Chapter 12: Reactions at the ga(B-carbon, part I -- Section 1: Review of acidity at the ga(B-carbon -- Section 2: Isomerization at the ga(B-carbon -- Section 3: Aldol addition -- Section 4: ga(B-carbon reactions in the synthesis lab - kinetic vs. thermodynamic alkylation products -- Interchapter: Predicting multistep pathways - the retrosynthesis approachChapter 13: Reactions at the ga(B-carbon, part II -- Section 1: Decarboxylation -- Section 2: An overview of fatty acid metabolism -- Section 3: Claisen condensation -- Section 4: Conjugate addition and elimination -- Section 5: Carboxylation -- Chapter 14: Electrophilic reactions -- Section 1: Electrophilic addition to alkenes -- Section 2: Elimination by the E1 mechanism -- Section 3: Electrophilic isomerization -- Section 4: Electrophilic substitution -- Section 5: Carbocation rearrangements -- Chapter 15: Oxidation and reduction reactions -- Section 1: Oxidation and reduction of organic compounds - an overview -- Section 2: Oxidation and reduction in the context of metabolism -- Section 3: Hydrogenation of carbonyl and imine groups -- Section 4: Hydrogenation of alkenes and dehydrogenation of alkanes -- Section 5: Monitoring hydrogenation and dehydrogenation reactions by UV spectroscopy -- Section 6: Redox reactions of thiols and disulfides -- Section 7: Flavin-dependent monooxygenase reactions: hydroxylation, epoxidation, and theBaeyer-Villiger oxidation -- Section 8: Hydrogen peroxide is a harmful 'Reactive Oxygen Species' -- Chapter 16: Radical reactions -- Section 1: Overview of single-electron reactions and free radicals -- Section 2: Radical chain reactions -- Section 3: Useful polymers formed by radical chain reactions -- Section 4: Destruction of the ozone layer by a radical chain reaction -- Section 5: Oxidative damage to cells, vitamin C, and scurvy -- Section 6: Flavin as a one-electron carrier -- Chapter 17: The organic chemistry of vitamins -- Section 1: Pyridoxal phosphate (Vitamin B6) -- Section 2: Thiamine diphosphate (Vitamin B1) -- Section 3: Thiamine diphosphate, lipoamide and the pyruvate dehydrogenase reaction -- Section 4: Folates
In English.
Description based on online resource
Keywords: Science -- Textbooks; Chemistry -- Textbooks